Effects of Gluten Intake on Risk of Celiac Disease: a case–control study on a Swedish birth cohort - Aronsson, Carin Andrén (Clin Gastroenterol Hepatol, 2015)
BACKGROUND & AIMS: It is not clear how intake of gluten during infancy affects subsequent risk of celiac disease. We investigated whether gluten intake before 2 years of age increases risk for celiac disease in genetically susceptible children. METHODS: We performed a case–control study of 436 pairs of children, generated from a database of 2525 children with genetic susceptibility to celiac disease in Sweden, matched for sex, birth year, and HLA genotype from September 2004 and February 2010. Children were screened annually for celiac disease using an assay for tissue transglutaminase autoantibodies (tTGA). Intestinal biopsies were collected from children who tested positive for tTGA to confirm the presence of celiac disease. Gluten intake was calculated from 3-day food records collected when the children were 9, 12, 18 and 24 months old. RESULTS: Breastfeeding duration (median 32 weeks) and age at first introduction to gluten (median 22 weeks) did not differ between cases and tTGA-negative children (controls). At the visit prior to tTGA seroconversion, cases reported a larger intake of gluten (median 4.9 g/day) than controls (median 3.9 g/day) (odds ratio [OR], 1.28; 95% confidence interval [CI], 1.13–1.46; P=.0002). More cases consumed amounts of gluten in the upper 3rd tertile (i.e. >5.0 g/day) before they tested positive for tTGA seroconversion than controls (OR, 2.65; 95% CI, 1.70–4.13; P<.0001). This increase in risk was similar for children homozygous for DR3-DQ2 (OR, 3.19; 95% CI, 1.61–6.30; P=.001), heterozygous for DR3-DQ2 (OR, 2.24; 95% CI, 1.08≥4.62; P=.030), and for children not carrying DR3-DQ2 (OR, 2.43; 95% CI, 0.90–6.54; P=.079). CONCLUSIONS: Intake of gluten before 2 years of age increases risk of celiac disease at least 2-fold in children with genetic risk factors for this disease. This association did not differ among HLA-DR3-DQ2 haplotypes. These findings may be taken into account for future infant feeding recommendations.